Characterizing nanoplastics‐induced stress and its SERS fingerprint in an intestinal membrane model. Issue 9 (1st April 2021) - Zhang, Qianyun; Reinhard, Björn M.
Abstract: Epithelium membranes provide important barrier functions, and it is important to understand how nanoparticle (NP) exposure affects their barrier function. In this manuscript, we investigate NP‐induced stress in a Caco‐2 intestinal epithelial membrane model and its effect on the vibrational spectrum of the extracellular medium that can be sampled and investigated without perturbation of the cells. Monolayers of Caco‐2 cells were incubated with 50 nm diameter polystyrene (PS) NPs functionalized with amine or carboxylic acid groups and concentrations of 1 × 10 12 –1 × 10 14 PS NPs mL –1 for 6 and 18 hours. Reactive oxygen species (ROS) generation, cell viability, and intestinal membrane integrity measurements were performed to detect and quantify PS NP‐induced membrane damage under the acute exposure conditions. After identifying conditions that result in NP‐induced stress, Surface Enhanced Raman Spectroscopy (SERS) was applied to monitor the composition of the medium in direct contact with the intestinal cells and to detect potential PS NP‐induced changes in the cellular metabolism in real time and in a minimally invasive fashion. The analysis of the SERS spectra through artificial intelligence algorithms and chemometric tools revealed concentration‐, exposure time‐, and surface chemistry‐dependent differences in the cellular metabolism in response to PS NPs. The SERS spectral analysis identifies the ring breathing mode of hypoxanthine (C4 H4 N4 O), as a spectroscopic marker for the PS NP‐induced loss in membrane integrity. Abstract : Nanoplastics‐induced stress in a Caco‐2 intestinal cell membrane model is characterized, and spectral markers in the extracellular medium are monitored by Surface Enhanced Raman Spectroscopy (SERS). Analysis of the SERS spectra through chemometrics and artificial intelligence identifies the ring breathing mode of hypoxanthine as a marker of nanoplastics‐induced cell membrane damage.